(untitled) (Journal of Economic Research & Business Administration, 2016)
It is agreed that issue of the shares by the company is one of the popular ways to attract financing for the company’s further development including production, high-tech and innovation spheres. The main purpose of the shares’ issue is to receive additional capital and attract investors. Receiving of financing on the public capital markets seeking for long-term investments is extensively used by private and state institutions in developed and developing countries all over the world and equity capital is one of these instruments. There some advantages and disadvantages that should be analyzed before going public and becoming an issuer. It is widely spread to make IPO by issuing shares on foreign markets, however not so many local companies issue shares to finance their activity or different projects. Large and mid-size companies have such kind of opportunities. There are some valuable advantages to receive money issuing securities. Whereas the shares’ issue is connected with risks that any listed company should manage.